Study of clinical and biochemical profile of scrub typhus in a tertiary care hospital of West Bengal - Rakesh Mandal; Sarmila Guha Banerjee; Arunima Sinha; Ujjwal Bandyopadhyay; Arijit Sinha (Asian Journal of Medical Sciences, 2023)
Background: Humans are accidental hosts in the zoonotic disease Scrub typhus. The disease though widespread in our county, it remains grossly underdiagnosed because of its non-septic clinical manifestations and lack of access to specific laboratory facilities.